The Income and Price Dependency of the Hungarian Sport Goods Consumption - Paár Dávid (PERIODICA POLYTECHNICA-SOCIAL AND MANAGEMENT SCIENCES, 2011)
Abstract The aim of the paper is to study the relationship of individuals’ sport goods consumption to personal income and relative sport price in Hungary in the period 1992-2006. It is shown, that the trend of the real sport goods consumption in conjunction with real income decreased till 2000 and it has been increasing since then. Income and price elasticity figures for both periods show, that sport goods consumption is price elastic, and sport goods are luxury goods for Hungarian households. Thus, without increased income – i.e. the average standard of living – a more sport conscious Hungarian population can hardly be imagined even if sport goods remained relatively cheap. Keywords sport goods consumption, net income, income elasticity, price elasticity